2003
DOI: 10.1038/sj.mp.4001306
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of lithium action: integration of lithium-responsive signaling and gene expression networks

Abstract: The clinical efficacy of lithium in the prophylaxis of recurrent affective episodes in bipolar disorder is characterized by a lag in onset and remains for weeks to months after discontinuation. Thus, the long-term therapeutic effect of lithium likely requires reprogramming of gene expression. Protein kinase C and glycogen synthase kinase-3 signal transduction pathways are perturbed by chronic lithium at therapeutically relevant concentrations and have been implicated in modulating synaptic function in nerve te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(79 citation statements)
references
References 108 publications
1
76
0
Order By: Relevance
“…Recent studies have shown that antidepressants and mood stabilizers regulate a variety of genes involved in cell survival and cell death, such as CREB, BDNF, Bcl-2, MAP kinases, and GSK-3beta (Manji and Duman, 2001;Lenox and Wang, 2003). Lithium carbonate, the major drug used to treat bipolar disorder, protects cultured rat brain neurons from NMDA-mediated excitotoxicity via mechanisms that include increased expression of Bcl-2 (Chuang et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that antidepressants and mood stabilizers regulate a variety of genes involved in cell survival and cell death, such as CREB, BDNF, Bcl-2, MAP kinases, and GSK-3beta (Manji and Duman, 2001;Lenox and Wang, 2003). Lithium carbonate, the major drug used to treat bipolar disorder, protects cultured rat brain neurons from NMDA-mediated excitotoxicity via mechanisms that include increased expression of Bcl-2 (Chuang et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…One possibility to explain this paradoxical fact is illustrated on Fig. 2: lithium interferes with the intracellular production of inositol triphosphate (IP3), via a specific inhibition of the enzyme inositol monophosphatase (IMPase) (16). The final effect of lithium on parathyroid chief cells might be the result of a balance between a weak activation at the level of the CASR and a stronger inhibition of intracellular pathways at the level of the IMPase.…”
Section: Mechanism Of Action Of Lithium On Parathyroid Cellsmentioning
confidence: 99%
“…The deficit of new drugs based on lithium is partly due to a complex mechanism of action; lithium affects several enzymes and cellular pathways simultaneously, making its most relevant molecular mechanism in the treatment of BD difficult to disentangle [310]. Nonetheless, it has become increasingly clear over the last 2 decades that one of the relevant (though by no means exclusive) mechanisms of action of lithium within the CNS is inhibition of GSK3, which mimics activation of Wnt/β-catenin signaling [311].…”
Section: Concluding Remarks: Therapeutic Considerationsmentioning
confidence: 99%